Uma análise do perfil do consumidor brasileiro de séries norte-americanas de televisão sob a perspectiva do fan funding - Leal, Maria Carolina Göpfert Palhano (2023)
The role of the TV show fan has been changing over time and technological innovations, especially regarding the interconnection allowed by Web 2.0. Campaigns known as Save Our Show, dedicated to save fan-favorite shows, are a fan labor tool. Fan labor can be translated into financial investment on the shows through crowdfunding campaigns in digital platforms. This practice is called fan funding, and the investors are known as fanvestors. This study aims to understand whether the Brazilian consumers for US TV shows are willing to fund such shows, turning themselves into fanvestors; as well as present successful Save Our Show movements that renewed the show or gave it closure by turning it into a movie; and analyze the changes on the role of the fan facing the technological development brought by the internet. To do so, it is needed to understand concepts like fan theory and Web 2.0. The study is divided in three steps. The first consists in bibliographic and documental search on the central themes such as fans and Web 2.0 and peripheral ones, such as social TV. The second step is dedicated to structuring the questionnaire and involves semi structured interviews with fans and a crowdfunding campaign ambassador. Lastly, the third step is the implementation of the closed questionnaire for Brazilian fans of US TV shows. The results of the research show the Brazilian fan is not willing to fund US TV shows, with 80% of the survey respondents claiming they would not donate any amount of money. The justifications include not being so attached to the show, preferring to donate money to more noble causes, and not having enough money to donate. The results presented reflect the political and economic environment Brazil is going though after a pandemic, and it is understood that it would be interesting to remake the study in a pandemic-free scenario